2017
DOI: 10.3389/fnins.2017.00387
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Mismatch Negativity in Response to Changes of Counter-Balanced Interaural Time and Level Differences

Abstract: Interaural time differences (ITD) and interaural level differences (ILD) both signal horizontal sound source location. To achieve a unified percept of our acoustic environment, these two cues require integration. In the present study, we tested this integration of ITD and ILD with electroencephalography (EEG) by measuring the mismatch negativity (MMN). The MMN can arise in response to spatial changes and is at least partly generated in auditory cortex. In our study, we aimed at testing for an MMN in response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Regarding the ERP study on sound localization, previous studies have found that changes of spatial cues (ITD, ILD, spectral cues) could evoke MMN response (100–130 ms) in auditory cortex (Altmann et al, 2017a , b ; Frey et al, 2017 ). In the present study, neurophysiological results did not show significant changes in terms of the early ERP components of N1 either between pre- and post-tests or between audiovisual and auditory only training groups.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the ERP study on sound localization, previous studies have found that changes of spatial cues (ITD, ILD, spectral cues) could evoke MMN response (100–130 ms) in auditory cortex (Altmann et al, 2017a , b ; Frey et al, 2017 ). In the present study, neurophysiological results did not show significant changes in terms of the early ERP components of N1 either between pre- and post-tests or between audiovisual and auditory only training groups.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the use of MMN neurofeedback training can improve a subject's ability to discriminate between two defined frequencies; however, the auditory discriminative abilities of healthy people have not been discussed. MMN steady induction traditionally requires more than 200 stimulation events (containing both standard and deviant) [20]. In the previous neurofeedback protocol, 20 stimulation events were adopted to calculate real-time MMN.…”
Section: Platform Validationmentioning
confidence: 99%